EFFICIENCY OF FIRE-FIGHTING PROTECTION OBJECTS IN PROVISION OF FIRE SAFETY AT INDUSTRIAL ENTERPRISES - A. V. Zhovna (Наука и техника)
The paper gives an analysis of economic results pertaining to organization of a system for fire-fighting protection of industrial enterprises in theRepublicofBelarus. Statistical data on operational conditions of technical means of fire-fighting protection, particularly, automatic systems for detection and extinguishing of fires, systems of internal fire-fighting water-supply.  Requirements and provisions  of normative and technical documents are thoroughly studied. Observance of these documents is to ensure the required level of  fire safety. On the basis of the obtained results concerning  economic analysis of efficiency optimization directions are defined for selection of technical means of fire-fighting protection at objects of industrial purpose.